FORMULASI DAN UJI EFEKTIFITAS SEDIAAN GEL EKSTRA ETANOL DAUN MANGROVE API-API (AVICENNIA MARINA) SEBAGAI ANTISEPTIK TANGAN - Titaley, Stany (PHARMACON, 2014)
Avicennia marina is a plant, that have anti-inflammation activity, antioxidant, antibacterial, andantivirus. Based on the compound owned, fire Mangrove (Avicennia marina) can be used as antiseptic hand. Purpose from this research is to formulate and test effect of hand antiseptic gel. Leaf extract gel stocks formulation fire Mangrove (Avicennia marina) has made with various concentration of extract that is 10%, 15%, and 20% with CMC-Na as it base. Use CMC-Na for the negative control and for positive control used Detol® Hand Sanitizer. For physical gel result include : organoleptic, homogenity and pH. Antiseptic gel testing was used replica method and testing data were analyzed by One Way Anova. The results of this research showed that leaf extract gel from fire Mangrove full fil the organoleptic quality parameters gel, homogeneity, pH and no have effect as hand antiseptic. Key words : leaf extract etanol gel from Mangrove Api-api (Avicennia marina), antiseptics, replica method